PENYULUHAN PEMANFAATAN BLOG UNTUK MEMBANGUN JIWA ENTREPRENEURSHIP PADA SISWA SMK KARTINI BATAM - Intan Utna Sari; Nora Nainggolan; Heryenzus (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service is carried out with the aim of being able to share the knowledge possessed with the students of SMK Kartini Batam City, Riau Islands. To be able to obtain the results of this devotion, the method used in this service is by providing service materials and providing training and assistance to the service participants. It is hoped that this service can have a positive effect on the students of SMK Kartini, Batam City, Riau Islands. The program target of the community service carried out is to refer to students so that they can take advantage of internet technology, especially blogs, as a bridge to build an entrepreneurial spirit from an early age. The activity was carried out at the pavilion of SMK Kartini running smoothly. The students followed the activity well, through a focused view attitude, a good listening attitude, it can be seen that students can understand the material presented by the devotees.